Konsep Pendidikan Wirausaha dan Kemandirian bagi Anak Panti Asuhan - Mubarok, Zahid; Tanjung, Hendri; Tamam, Abbas Mansur (Ta'dibuna: Jurnal Pendidikan Islam, 2018)
The problem of education in Indonesia at this time has not produced independent students. Education held in schools or other educational institutions also lacks creativity for students and has not yet produced innovative students and has not been able to motivate high learning. There are still many educational institutions that do not teach entrepreneurship education. Entrepreneurial education has not been widely invested in students from an early age. This research is qualitative research (qualitative research) . The data in this study were obtained through library research ( library research).) The data compiled consists of written materials that have been published in the form of books, journals and magazines as well as from the internet that have direct and indirect links with this research. Entrepreneurship education aims to form a whole person ( holistic), as a person who has the character, understanding and skills as an entrepreneur, so the results are obtained awareness of the importance of values, the formation of the character of entrepreneurship into the behavior of students everyday through the learning process. An entrepreneur in his mind always tries to find, utilize, and create business opportunities that can provide benefits. Loss risk is normal because it holds the principle that a loss factor must exist. In fact, the greater the risk of loss that will be faced, the greater the profit opportunities that can be achieved. There is no loss term as long as someone does business with courage and calculation. This is what is called the entrepreneurial spirit.